Community Forum: An Effective Program Planning Tool - Lisa A. Guion (EDIS)
One means by which educators can promote dialog about the needs in the county among diverse groups of constituents and stakeholders is to hold a community forum. A community forum is an excellent program-planning tool because it can promote thoughtful discussions where many different points of view are shared. It also affords community members the opportunity to share specific information about emerging program opportunities and needs, as well as provide broadbased input from key clientele groups concerning their priorities for future educational programs. This document is PE070, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville, FL 32611: First published: October 2003.